The Hainanese Temples of Singapore: A Case Study of the Hougang Shui Wei Sheng Niang Temple and Its Lantern Festival Celebration - Ji, Yiwen (Religions, 2020)
Shui Wei Sheng Niang (水尾圣娘) Temple is located within a united temple at 109a, Hougang Avenue 5, Singapore. Shui Wei Sheng Niang is a Hainanese goddess, the worship of whom is widespread in Hainanese communities in South East Asia. This paper examines a specific Hainanese temple and how its rituals reflect the history of Hainanese immigration to Singapore. The birthday rites of the goddess (Lantern Festival Celebration) are held on the 4th and 14th of the first lunar month. This paper also introduces the life history and ritual practices of a Hainanese Daoist master and a Hainanese theater actress.